2011
DOI: 10.1002/smi.1402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effects of Lavender and Peppermint Aromatherapy Using Sensitive Salivary Endocrinological Stress Markers

Abstract: By measuring the sensitive salivary endocrinological stress markers cortisol and chromogranin A (CgA), we investigated effects on stress of lavender and peppermint aromas. Groups of volunteers were each exposed to an airborne organic essential oil: either lavender or peppermint or, for control, odourless jojoba. Saliva samples were collected immediately before and after the 10‐min exposure and 5 and 10 min later. Salivary cortisol and CgA levels were evaluated by enzyme‐linked immunosorbent assay. After exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
(38 reference statements)
0
14
1
Order By: Relevance
“…Some studies, however, have reported no positive effects [25][26][27]. To the best of our knowledge, a limited number of studies have been done on the effect of peppermint on the sleep quality of cancer patients, which have shown its positive effect on improving the sleep quality [28,29]. e results of a systematic review performed in 2016 showed the low reliability of most studies in the field of aromatherapy in cancer patients, hence, suggesting further studies in this regard [30].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, however, have reported no positive effects [25][26][27]. To the best of our knowledge, a limited number of studies have been done on the effect of peppermint on the sleep quality of cancer patients, which have shown its positive effect on improving the sleep quality [28,29]. e results of a systematic review performed in 2016 showed the low reliability of most studies in the field of aromatherapy in cancer patients, hence, suggesting further studies in this regard [30].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, results obtained in some of these studies are controversial. Whereas expected decreases in sCgA [25,26,29,32,33,38], or attenuation of sCgA increases [28,30] were observed in some studies, others report raises in sCgA concentrations [27,31,[34][35][36], and mostly explain the increase as related to positive eustress or stress relieving characteristics of the performed activity. Moreover, the effect of a relaxing activity such as spa bathing on sCgA has been described as dependent on the subjects' background stress level: the high-stress group showed lower sCgA levels after spa bathing while the low-stress group presented higher sCgA levels in the same conditions [37].…”
Section: Discussionmentioning
confidence: 87%
“…sCgA has been used to evaluate psychophysiological changes in stressful situations or activities already mentioned [8,9,[11][12][13][14], usually reporting fast increases in this biomarker concentration. sCgA has been also employed to assess improvement resulting from healthcare modalities-such as aromatherapy [25][26][27], consumption of green tea [28], ingestion of enzyme-treated asparagus extract [29], and Cimifuga racemosa extract administration [30]-or from stress-relieving activities, such as laughter [31,32], gum chewing [33], woodland walking [34,35], short leisure trips [36], spa bathing [37], or exposure to negative air ions [38]. Nevertheless, results obtained in some of these studies are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The oils of Lavandula varieties have also proven to be effective in reducing stress, anxiety, and depression in patients in an array of clinical settings such as hospice cancer patients, patients awaiting treatment in a dental office, male and female volunteers shown anxiety-provoking film clips, pregnant women through use of L. angustifolia essential oil-containing cream, as well as reduction of anxiety and heart rate in patients undergoing elective cosmetic procedures [127][128][129][130][131]. One study suggested that the reduction of stress symptoms upon inhalation of the essential oils may be partially due to the reduction in salivary cortisol levels, and to protection against oxidative stress by increasing free radical scavenging activity [132,133]. Lavender aromatherapy has also exhibited positive effects on heart disease with increased relaxation, reduced serum cortisol levels, and increased coronary circulation with improved coronary flow velocity reserve (CFVR) in healthy adult men [134].…”
Section: Psychological Implicationsmentioning
confidence: 99%